The Effectiveness of Extracorporeal Shock Wave Therapy in Lower Limb Tendinopathy: A Systematic Review. (March 2015) - Mani-Babu, Sethu; Morrissey, Dylan; Waugh, Charlotte; Screen, Hazel; Barton, Christian
Background: There is accumulating evidence for the effectiveness of extracorporeal shock wave therapy (ESWT) when treating lower limb tendinopathies including greater trochanteric pain syndrome (GTPS), patellar tendinopathy (PT), and Achilles tendinopathy (AT). Purpose: To evaluate the effectiveness of ESWT for lower limb tendinopathies. Study Design: Systematic review and meta-analysis. Methods: PubMed (Medline), Embase, Web of Knowledge, Cochrane, and CINAHL were searched from inception to February 2013 for studies of any design investigating the effectiveness of ESWT in GTPS, PT, and AT. Citation tracking was performed using PubMed and Google Scholar. Animal and non–English language studies were excluded. A quality assessment was performed by 2 independent reviewers, and effect size calculations were computed when sufficient data were provided. Results: A total of 20 studies were identified, with 13 providing sufficient data to compute effect size calculations. The energy level, number of impulses, number of sessions, and use of a local anesthetic varied between studies. Additionally, current evidence is limited by low participant numbers and a number of methodological weaknesses including inadequate randomization. Moderate evidence indicates that ESWT is more effective than home training and corticosteroid injection in the short (<12 months) and long (>12 months) term for GTPS. Limited evidence indicates that ESWT is more effective than alternative nonoperative treatments including nonsteroidal anti-inflammatory drugs, physical therapy, and an exercise program and equal to patellar tenotomy surgery in the long term for PT. Moderate evidence indicates that ESWT is more effective than eccentric loading for insertional AT and equal to eccentric loading for midportion AT in the short term. Additionally, there is moderate evidence that combining ESWT and eccentric loading in midportion AT may produce superior outcomes to eccentric loading alone. Conclusion: Extracorporeal shock wave therapy is an effective intervention and should be considered for GTPS, PT, and AT particularly when other nonoperative treatments have failed.